The diva spices it up - Davis, Krista (Davis, Krista. Domestic diva mystery, 2021)
"Sophie never considered ghostwriting as a side gig, until former actress and aspiring lifestyle guru, Tilly Stratford, trophy wife of Wesley Winthrope, needs someone to write her celebrity cookbook. Sophie agrees, hoping she'll earn enough bread on this assignment to finish her bathroom renovations. But as it turns out, Sophie isn't the first foodie to get a taste for recipe ghostwriting, and if the marginalia are any indication, this project could be a killer... Wesley claims professional ghostwriter Abby Bergeron suddenly abandoned Tilly's cookbook with no warning. But Sohpie quickly discovers that Abby may be more ghost than writer now...and her disappearance was no accident. So Sophie cracks open a fresh investigation, but sifting the seasoned murderer from this sampling of salty suspects won't be easy. Will Sophie savor another case closed or will the culprit simply melt away?"--Provided by publisher.